A 3D printed implant with surface functionalization and preparation method thereof
By introducing sodium alginate and HPMC into the titanium alloy implant and subjecting electrolytic treatment and functionalization, the problem of insufficient vanadium ion release and fatigue performance of the titanium alloy implant in the body is solved, and better biocompatibility and mechanical properties are achieved.
Patent Information
- Application Number
- CN202510035386.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-08
AI Technical Summary
Existing titanium alloy implants may release vanadium ions in the body, resulting in cytotoxicity and immune responses, and their fatigue performance is poor under dynamic loads, prone to crack propagation and fracture.
Compound titanium alloy paste was prepared by compounding sodium alginate with HPMC and introducing it onto Ti6Al4V powder, and implants were prepared by 3D printing. Then, the implant was subjected to surface functionalization using electrolytic treatment and treatment solution of polydopamine and silane coupling agent.
It improves the biocompatibility and mechanical properties of the implant, enhances the binding force between the implant and the host bone, alleviates the stress concentration phenomenon, and improves the crack propagation resistance and wear resistance.
Smart Images

Figure CN119770746A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of 3D printing materials, and in particular to a 3D printing implant with surface functionalization treatment and a preparation method thereof. Background Art
[0002] 3D printing technology has shown great potential in the manufacture of personalized medical implants, especially in the fields of orthopedics, dentistry, craniofacial surgery, etc. In orthopedics, 3D printing can produce structures with micro-nano pores, promote new bone growth, and increase the bonding force between implants and host bones. The main materials of 3D printed implants include titanium alloys, cobalt-chromium alloys, and high molecular organic matter. Among them, titanium and its alloys have low density but high strength, can withstand greater mechanical stress, and at the same time reduce the pressure of implants on surrounding tissues. It also has excellent biocompatibility and corrosion resistance, so it is considered to be one of the most suitable metal materials for long-term implantation in the human body.
[0003] The main component of existing titanium alloy implants is Ti6Al4V, which has excellent mechanical properties and biocompatibility. However, vanadium ions may be released in the body, and studies have shown that vanadium has certain cytotoxicity, which may affect the normal functions of bone cells and other tissue cells. In addition, a small number of patients may be sensitive to vanadium, triggering local or systemic immune responses. At the same time, although Ti6Al4V has high tensile strength, its fatigue performance is relatively poor under dynamic loads, especially in complex stress environments, and crack extension and fracture are prone to occur. Therefore, the present invention provides a 3D printed implant with surface functionalization treatment and a preparation method thereof to solve the above-mentioned existing problems. Summary of the invention
[0004] In view of the shortcomings of the prior art, the object of the present invention is to provide a 3D printed implant with surface functionalization treatment and a preparation method thereof.
[0005] A method for preparing a 3D printed implant with a surface functionalized treatment, comprising the following steps:
[0006] S1: Preparation of PVA / PEG / GO hydrogel
[0007] Weigh PVA solid, add deionized water, seal, heat, and stir to obtain a PVA solution; weigh PEG powder, dissolve it in deionized water, and stir to obtain a PEG solution; mix the PVA solution, PEG solution, and GO solution to obtain a PVA / PEG / GO hydrogel;
[0008] S2: Preparation of Ti6Al4V composite powder
[0009] Sodium alginate, HPMC and deionized water are mixed, heated and stirred to obtain a premixed liquid, Ti6Al4V powder is weighed, heated, and then all added to the premixed liquid, and a foaming agent is added and stirred to obtain a Ti6Al4V composite slurry, the Ti6Al4V composite slurry is poured into a mold, and low-temperature solidified to obtain a Ti6Al4V composite embryo body, the Ti6Al4V composite embryo body is sintered, and then crushed, sieved, and granulated to obtain a Ti6Al4V composite powder;
[0010] S3: Preparation of 3D printed implants
[0011] S3.1: stirring the PVA / PEG / GO hydrogel and adding the Ti6Al4V composite powder to obtain a composite titanium alloy slurry, adding the composite titanium alloy slurry into a syringe for 3D printing, drying, then degreasing, and sintering to obtain a 3D printed implant;
[0012] S4: Surface treatment of 3D printed implants
[0013] S4.1: Sodium hydroxide, sodium dihydrogen phosphate, disodium ethylenediaminetetraacetic acid, calcium acetate and deionized water are mixed to prepare an electrolyte, a 3D printed implant is placed in the electrolyte, the 3D printed implant is used as an anode and the electrolytic cell is used as a cathode, and an electric current is applied to obtain an electrically treated 3D printed implant, the electrically treated 3D printed implant is immersed in a sodium hydroxide solution, heated, then taken out, immersed in a mixture of a polydopamine solution and a silane coupling agent, then taken out, rinsed with deionized water, and dried to obtain a 3D printed implant with surface functionalization treatment.
[0014] Furthermore, the preparation of PVA / PEG / GO hydrogel in step S1 comprises the following steps:
[0015] S1.1: Weigh 10-12 parts by mass of PVA solid, add 80-90 parts by mass of deionized water, seal, heat to 70-80°C, and stir at a speed of 50-60 r / min until all the PVA is dissolved to obtain a PVA solution;
[0016] S1.2: Weigh 20-25 parts by weight of PEG powder, dissolve it in 80-85 parts by weight of deionized water, and stir for 1-5 minutes to obtain a PEG solution;
[0017] S1.3: PVA solution, PEG solution and GO solution were mixed in a volume ratio of (4-6):(2-5):1, heated to 60-70°C, and ultrasonically treated for 10-20 min to obtain PVA / PEG / GO hydrogel.
[0018] Furthermore, the preparation of Ti6Al4V composite powder in step S2 comprises the following steps:
[0019] S2.1: 1-5 parts by mass of sodium alginate, 0.5-3 parts by mass of HPMC and 95-100 parts by mass of deionized water are mixed, heated to 80-90° C., and magnetically stirred at a speed of 400-450 r / min for 2-2.5 h to obtain a premixed solution;
[0020] S2.2: Weigh 5-10 parts by mass of Ti6Al4V powder, heat it to 80-90°C, then add all of it to the premixed liquid, heat it in a water bath to maintain the temperature at 80-90°C, continue stirring for 30-35 minutes, then add 8-12 parts by mass of a foaming agent, stir for 10-20 minutes, and obtain a Ti6Al4V composite slurry;
[0021] S2.3: pouring the Ti6Al4V composite slurry into a mold and curing it in a low temperature environment of 0-4°C for 10-12 hours, and then maintaining the temperature at 15-20°C for air drying for 24-26 hours to obtain a Ti6Al4V composite embryo;
[0022] S2.4: The Ti6Al4V composite body is placed in a vacuum sintering furnace in an argon atmosphere for sintering at a temperature of 1000-1400°C. After sintering, it is naturally cooled to room temperature 24°C, and then crushed through a 100-mesh sieve and granulated to obtain a Ti6Al4V composite powder.
[0023] Furthermore, the foaming agent is fatty alcohol polyoxyethylene ether.
[0024] Furthermore, the preparation of the 3D printed implant in step S3 comprises the following steps:
[0025] S3.1: Stir the PVA / PEG / GO hydrogel at a speed of 1500-1600 r / min, add the Ti6Al4V composite powder, the mass ratio of the PVA / PEG / GO hydrogel to the Ti6Al4V composite powder is 9:(10-12), stir for 20-25 min, and obtain a composite titanium alloy slurry;
[0026] S3.2: Add the composite titanium alloy slurry into the syringe, select a printing head with a diameter of 0.5 mm, set the extrusion speed to 1000 mm·min-1, and print out the titanium alloy stent blank according to the planned path. The stent size is set to 30 mm in length, 30 mm in width, and 10 mm in height. The diameter of a single filament is 0.5 mm, and the stent hole type is a vertical orthogonal structure. Place the stent blank in a 65-70℃ drying oven and dry it for 6-8 hours. Then, complete degreasing and sintering in a vacuum tube furnace less than 2×10-2Pa, and keep it warm for 2-2.5 hours to obtain a 3D printed implant.
[0027] Furthermore, the sintering temperature in the vacuum tube furnace is 1100-1350°C.
[0028] Furthermore, the 3D printed implant surface treatment in step S4 comprises the following steps:
[0029] S4.1: 0.2 mol / L sodium hydroxide, 0.04 mol / L sodium dihydrogen phosphate, 0.015 mol / L disodium ethylenediaminetetraacetate, 0.1 mol / L calcium acetate and deionized water are mixed in a volume ratio of 2:3:1:1:(8-10) to prepare an electrolyte, the 3D printed implant is placed in the electrolyte, the 3D printed implant is used as the anode and the electrolytic cell is used as the cathode, the temperature is maintained at 30-35°C, and a pulsating power supply is applied for 5-10 minutes to obtain an electrically treated 3D printed implant;
[0030] S4.2: Immerse the electrically treated 3D printed implant in a 5 mol / L sodium hydroxide solution, in a water bath at 65-70°C for 24-26 hours, then heat to 80-90°C, take it out, immerse it in a mixture of polydopamine solution and silane coupling agent for 1-1.5 hours, then take it out, rinse it with deionized water 3 times, and dry it at 60-80°C for 4-5 hours to obtain a 3D printed implant with surface functionalization treatment.
[0031] Furthermore, the silane coupling agent is 3-aminopropyltriethoxysilane.
[0032] Furthermore, the volume ratio of the polydopamine solution to the silane coupling agent is 3:1.
[0033] A 3D printed implant with a surface functionalization treatment is prepared by the above-mentioned method for preparing a 3D printed implant with a surface functionalization treatment.
[0034] Compared with the prior art, the present invention has at least the following beneficial effects:
[0035] 1. The present invention compounds sodium alginate and HPMC and introduces them into Ti6Al4V powder. Both sodium alginate and HPMC are biodegradable materials with good cell affinity and blood compatibility, and will not cause obvious immune response or toxicity. In addition, sodium alginate and HPMC can simulate the calcium-phosphorus deposition process in bone tissue, promote new bone formation, and enhance the bonding force between the implant and the host bone. After introduction, sodium alginate and HPMC exist on the surface of Ti6Al4V powder in the form of a coating, which can alleviate the stress concentration phenomenon of the implant formed by Ti6Al4V powder after implantation, and improve the crack propagation resistance and wear resistance of the implant. In addition, due to the good biocompatibility of the two, the stiffness difference between the metal substrate and the soft tissue can be reduced, the stress shielding effect that may occur after long-term implantation can be reduced, and the compressive strength of the 3D printed implant can be improved.
[0036] 2. The present invention uses a treatment liquid formed by mixing polydopamine and a silane coupling agent to treat the electrically treated 3D printed implant. This combination not only improves the biocompatibility and mechanical properties of the titanium alloy, but also brings functional modification to the 3D printed implant. The silane coupling agent has an organic functional group at one end and a siloxane group at the other end, which can bridge interfaces of different properties. The functional group is introduced on the surface of the titanium alloy through the silane coupling agent, thereby improving the binding ability of polydopamine and the 3D printed implant to form a coating. The polydopamine coating can simulate the calcium-phosphorus deposition process in natural bone tissue, promote new bone formation, thereby enhancing the bonding force between the implant and the host bone, and improving the biocompatibility of the 3D printed implant. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable those skilled in the relevant art to make and use the present disclosure.
[0038] Figure 1 This is a flow chart of a method for preparing a 3D printed implant with surface functionalization used in an embodiment of the present invention. DETAILED DESCRIPTION
[0039] The following is a detailed description of a surface functionalized 3D printed implant and a preparation method thereof provided by the present invention in combination with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies; and the accompanying drawings are only for a more specific description of the embodiments, and are not intended to specifically limit the present invention.
[0040] Embodiment 1:
[0041] A method for preparing a 3D printed implant with a surface functionalized treatment, such as Figure 1 As shown, the following steps are included:
[0042] S1: Preparation of PVA / PEG / GO hydrogel
[0043] S1.1: Weigh 10 parts by mass of PVA solid, add 80 parts by mass of deionized water, seal, heat to 70°C, and stir at a speed of 50 r / min until all the PVA is dissolved to obtain a PVA solution;
[0044] S1.2: Weigh 20 parts by weight of PEG powder, dissolve it in 80 parts by weight of deionized water, and stir for 1 minute to obtain a PEG solution;
[0045] S1.3: PVA solution, PEG solution and GO solution were mixed in a volume ratio of 4:2:1, heated to 60 °C, and ultrasonically treated for 10 min to obtain PVA / PEG / GO hydrogel.
[0046] S2: Preparation of Ti6Al4V composite powder
[0047] S2.1: 1 part by mass of sodium alginate, 0.5 part by mass of HPMC and 95 parts by mass of deionized water were mixed, heated to 80°C, and magnetically stirred at a speed of 400 r / min for 2 h to obtain a premixed solution;
[0048] S2.2: Weigh 5 parts by mass of Ti6Al4V powder and heat it to 80°C, then add all of it to the premixed liquid, heat it in a water bath to maintain the temperature at 80°C, continue stirring for 30 minutes, then add 8 parts by mass of a foaming agent, fatty alcohol polyoxyethylene ether, and stir for 10 minutes to obtain a Ti6Al4V composite slurry;
[0049] S2.3: pouring the Ti6Al4V composite slurry into a mold and curing it at a low temperature of 0°C for 10 hours, and then air-drying it at 15°C for 24 hours to obtain a Ti6Al4V composite embryo;
[0050] S2.4: The Ti6Al4V composite body is placed in a vacuum sintering furnace in an argon atmosphere for sintering at a temperature of 1000°C. After sintering, it is naturally cooled to room temperature of 24°C, and then crushed through a 100-mesh sieve and granulated to obtain a Ti6Al4V composite powder.
[0051] S3: Preparation of 3D printed implants
[0052] S3.1: PVA / PEG / GO hydrogel was stirred at a speed of 1500 r / min, and Ti6Al4V composite powder was added, the mass ratio of PVA / PEG / GO hydrogel to Ti6Al4V composite powder was 9:10, and stirred for 20 min to obtain composite titanium alloy slurry;
[0053] S3.2: Add the composite titanium alloy slurry into the syringe, select a printing head with a diameter of 0.5 mm, set the extrusion speed to 1000 mm / min, and print out the titanium alloy stent blank according to the planned path. The stent size is set to 30 mm in length, 30 mm in width, and 10 mm in height. The diameter of a single wire is 0.5 mm, and the stent hole type is a vertical orthogonal structure. The stent blank is placed in a drying oven at 65 °C for 6 h, and then dried at less than 2 × 10 -2 Debinding and sintering were completed in a vacuum tube furnace at Pa with a sintering temperature of 1100 °C and a heat preservation time of 2 h to obtain a 3D printed implant.
[0054] S4: Surface treatment of 3D printed implants
[0055] S4.1: 0.2 mol / L sodium hydroxide, 0.04 mol / L sodium dihydrogen phosphate, 0.015 mol / L disodium ethylenediaminetetraacetate, 0.1 mol / L calcium acetate and deionized water are mixed in a volume ratio of 2:3:1:1:8 to prepare an electrolyte, the 3D printed implant is placed in the electrolyte, the 3D printed implant is used as the anode and the electrolytic cell is used as the cathode, the temperature is maintained at 30°C, and a pulsating power supply is applied for 5 minutes to obtain an electrically treated 3D printed implant;
[0056] S4.2: The electrically treated 3D printed implant was immersed in a 5 mol / L sodium hydroxide solution, placed in a water bath at 65°C for 24 hours, then heated to 80°C, taken out, immersed in a mixture of polydopamine solution and silane coupling agent for 1 hour, the volume ratio of polydopamine solution to silane coupling agent being 3:1, and the silane coupling agent being 3-aminopropyltriethoxysilane. Then, the implant was taken out, rinsed with deionized water 3 times, and dried at 60°C for 4 hours to obtain a 3D printed implant with surface functionalization treatment.
[0057] Embodiment 2:
[0058] A method for preparing a 3D printed implant with a surface functionalized treatment, such as Figure 1 As shown, the following steps are included:
[0059] S1: Preparation of PVA / PEG / GO hydrogel
[0060] S1.1: Weigh 12 parts by mass of PVA solid, add 90 parts by mass of deionized water, seal, heat to 70°C, and stir at a speed of 50 r / min until all the PVA is dissolved to obtain a PVA solution;
[0061] S1.2: Weigh 25 parts by weight of PEG powder, dissolve it in 85 parts by weight of deionized water, and stir for 1 minute to obtain a PEG solution;
[0062] S1.3: PVA solution, PEG solution and GO solution were mixed in a volume ratio of 6:5:1, heated to 60 °C, and ultrasonically treated for 10 min to obtain PVA / PEG / GO hydrogel.
[0063] S2: Preparation of Ti6Al4V composite powder
[0064] S2.1: 5 parts by mass of sodium alginate, 3 parts by mass of HPMC and 100 parts by mass of deionized water were mixed, heated to 80°C, and magnetically stirred at a speed of 400 r / min for 2 h to obtain a premixed solution;
[0065] S2.2: Weigh 10 parts by mass of Ti6Al4V powder, heat it to 80°C, then add all of it to the premixed liquid, heat it in a water bath to maintain the temperature at 80°C, continue stirring for 30 minutes, then add 12 parts by mass of a foaming agent, fatty alcohol polyoxyethylene ether, stir for 10 minutes, and obtain a Ti6Al4V composite slurry;
[0066] S2.3: pouring the Ti6Al4V composite slurry into a mold and curing it at a low temperature of 0°C for 10 hours, and then air-drying it at 15°C for 24 hours to obtain a Ti6Al4V composite embryo;
[0067] S2.4: The Ti6Al4V composite body is placed in a vacuum sintering furnace in an argon atmosphere for sintering at a temperature of 1000°C. After sintering, it is naturally cooled to room temperature of 24°C, and then crushed through a 100-mesh sieve and granulated to obtain a Ti6Al4V composite powder.
[0068] S3: Preparation of 3D printed implants
[0069] S3.1: PVA / PEG / GO hydrogel was stirred at a speed of 1500 r / min, and Ti6Al4V composite powder was added, the mass ratio of PVA / PEG / GO hydrogel to Ti6Al4V composite powder was 9:12, and stirred for 20 min to obtain composite titanium alloy slurry;
[0070] S3.2: Add the composite titanium alloy slurry into the syringe, select a printing head with a diameter of 0.5 mm, set the extrusion speed to 1000 mm / min, and print out the titanium alloy stent blank according to the planned path. The stent size is set to 30 mm in length, 30 mm in width, and 10 mm in height. The diameter of a single wire is 0.5 mm, and the stent hole type is a vertical orthogonal structure. The stent blank is placed in a drying oven at 65 °C for 6 h, and then dried at less than 2 × 10 -2 Debinding and sintering were completed in a vacuum tube furnace at Pa with a sintering temperature of 1100 °C and a heat preservation time of 2 h to obtain a 3D printed implant.
[0071] S4: Surface treatment of 3D printed implants
[0072] S4.1: 0.2 mol / L sodium hydroxide, 0.04 mol / L sodium dihydrogen phosphate, 0.015 mol / L disodium ethylenediaminetetraacetate, 0.1 mol / L calcium acetate and deionized water are mixed in a volume ratio of 2:3:1:1:10 to prepare an electrolyte, the 3D printed implant is placed in the electrolyte, the 3D printed implant is used as the anode and the electrolytic cell is used as the cathode, the temperature is maintained at 30°C, and a pulsating power supply is applied for 5 minutes to obtain an electrically treated 3D printed implant;
[0073] S4.2: The electrically treated 3D printed implant was immersed in a 5 mol / L sodium hydroxide solution, placed in a water bath at 65°C for 24 hours, then heated to 80°C, taken out, immersed in a mixture of polydopamine solution and silane coupling agent for 1 hour, the volume ratio of polydopamine solution to silane coupling agent being 3:1, and the silane coupling agent being 3-aminopropyltriethoxysilane. Then, the implant was taken out, rinsed with deionized water 3 times, and dried at 60°C for 4 hours to obtain a 3D printed implant with surface functionalization treatment.
[0074] Embodiment 3:
[0075] A method for preparing a 3D printed implant with a surface functionalized treatment, such as Figure 1 As shown, the following steps are included:
[0076] S1: Preparation of PVA / PEG / GO hydrogel
[0077] S1.1: Weigh 10 parts by mass of PVA solid, add 80 parts by mass of deionized water, seal, heat to 80°C, and stir at a speed of 60 r / min until all the PVA is dissolved to obtain a PVA solution;
[0078] S1.2: Weigh 20 parts by weight of PEG powder, dissolve it in 80 parts by weight of deionized water, and stir for 5 minutes to obtain a PEG solution;
[0079] S1.3: PVA solution, PEG solution and GO solution were mixed in a volume ratio of 4:2:1, heated to 70 °C, and ultrasonically treated for 20 min to obtain PVA / PEG / GO hydrogel.
[0080] S2: Preparation of Ti6Al4V composite powder
[0081] S2.1: 1 part by mass of sodium alginate, 0.5 part by mass of HPMC and 95 parts by mass of deionized water were mixed, heated to 90°C, and magnetically stirred at a speed of 450 r / min for 2.5 h to obtain a premixed solution;
[0082] S2.2: Weigh 5 parts by mass of Ti6Al4V powder and heat it to 90°C, then add all of it to the premixed liquid, heat it in a water bath to maintain the temperature at 90°C, continue stirring for 30 minutes, then add 8 parts by mass of a foaming agent, fatty alcohol polyoxyethylene ether, and stir for 20 minutes to obtain a Ti6Al4V composite slurry;
[0083] S2.3: pouring the Ti6Al4V composite slurry into a mold and curing it in a low temperature environment of 4°C for 12 hours, and then air-drying it at 20°C for 26 hours to obtain a Ti6Al4V composite embryo;
[0084] S2.4: The Ti6Al4V composite body is placed in a vacuum sintering furnace in an argon atmosphere for sintering at a temperature of 1400°C. After sintering, it is naturally cooled to room temperature of 24°C, and then crushed through a 100-mesh sieve and granulated to obtain a Ti6Al4V composite powder.
[0085] S3: Preparation of 3D printed implants
[0086] S3.1: PVA / PEG / GO hydrogel was stirred at a speed of 1600 r / min, and Ti6Al4V composite powder was added, the mass ratio of PVA / PEG / GO hydrogel to Ti6Al4V composite powder was 9:10, and stirred for 25 min to obtain composite titanium alloy slurry;
[0087] S3.2: Add the composite titanium alloy slurry into the syringe, select a printing head with a diameter of 0.5 mm, set the extrusion speed to 1000 mm / min, and print out the titanium alloy stent blank according to the planned path. The stent size is set to 30 mm in length, 30 mm in width, and 10 mm in height. The diameter of a single wire is 0.5 mm, and the stent hole type is a vertical orthogonal structure. The stent blank is placed in a drying oven at 65 °C for 6 h, and then dried at less than 2 × 10 -2 Debinding and sintering were completed in a vacuum tube furnace at Pa with a sintering temperature of 1100 °C and a heat preservation time of 2 h to obtain a 3D printed implant.
[0088] S4: Surface treatment of 3D printed implants
[0089] S4.1: 0.2 mol / L sodium hydroxide, 0.04 mol / L sodium dihydrogen phosphate, 0.015 mol / L disodium ethylenediaminetetraacetate, 0.1 mol / L calcium acetate and deionized water are mixed in a volume ratio of 2:3:1:1:8 to prepare an electrolyte, the 3D printed implant is placed in the electrolyte, the 3D printed implant is used as the anode and the electrolytic cell is used as the cathode, the temperature is maintained at 35°C, and a pulsating power supply is applied for 10 minutes to obtain an electrically treated 3D printed implant;
[0090] S4.2: The electrically treated 3D printed implant was immersed in a 5 mol / L sodium hydroxide solution, in a water bath at 65°C for 26 h, then heated to 90°C, taken out, immersed in a mixture of polydopamine solution and silane coupling agent for 1.5 h, the volume ratio of polydopamine solution to silane coupling agent being 3:1, and the silane coupling agent being 3-aminopropyltriethoxysilane, then taken out, rinsed with deionized water three times, and dried at 80°C for 5 h to obtain a 3D printed implant with surface functionalization treatment.
[0091] Comparative Example 1:
[0092] Compared with Example 1, the difference of Comparative Example 1 is that sodium alginate is not added in step S2.1, specifically "S2.1: mix 0.5 parts by mass of HPMC and 95 parts by mass of deionized water, heat to 80°C, and magnetically stir at a speed of 400 r / min for 2 hours to obtain a premixed solution". The prepared surface functionalized 3D printed implant is recorded as Comparative Example 1.
[0093] Comparative Example 2:
[0094] Compared with Example 1, the difference of Comparative Example 2 is that HPMC is not added in step S2.1, specifically: "S2.1: Mix 1 mass part of sodium alginate, 0.5 mass part of HPMC and 95 mass parts of deionized water, heat to 80°C, and magnetically stir at a speed of 400 r / min for 2 hours to obtain a premixed solution", and the prepared surface functionalized 3D printed implant is recorded as Comparative Example 2.
[0095] Comparative Example 3:
[0096] Compared with Example 1, the difference of Comparative Example 3 is that no polydopamine solution is added in step S4.2, specifically: "S4.2: immerse the electrically treated 3D printed implant in a 5 mol / L sodium hydroxide solution, bathe at 65°C for 24 hours, then heat to 80°C, then take it out, immerse it in a silane coupling agent for 1 hour, the silane coupling agent is 3-aminopropyltriethoxysilane, then take it out, rinse it with deionized water 3 times, and dry it at 60°C for 4 hours to obtain a surface functionalized 3D printed implant", and the prepared surface functionalized 3D printed implant is recorded as Comparative Example 3.
[0097] Comparative Example 4:
[0098] Compared with Example 1, the difference of Comparative Example 4 is that no silane coupling agent is added in step S4.2, specifically: "S4.2: immersing the electrically treated 3D printed implant in a 5 mol / L sodium hydroxide solution, bathing at 65°C for 24 hours, then heating to 80°C, then taking it out, immersing it in a polydopamine solution for 1 hour, then taking it out, rinsing it with deionized water 3 times, and drying it at 60°C for 4 hours to obtain a surface functionalized 3D printed implant", and the prepared surface functionalized 3D printed implant is recorded as Comparative Example 4.
[0099] A compression test was performed on Examples 1-3 and Comparative Examples 1-4 at room temperature using a Zwick / Roell Z020 universal material testing machine. The compression rate in the experiment was 1 mm / min. The compressive strengths obtained are shown in Table 1.
[0100] Table 1
[0101] Compressive strength(MPa) Example 1 77.8 Example 2 74.6 Example 3 75.2 Comparative Example 1 62.4 Comparative Example 2 63.7 Comparative Example 3 68.1 Comparative Example 4 64.6
[0102] The compressive strength of Examples 1-3 is above 74.6 MPa, which is higher than that of the comparative example. It can be seen that the 3D printed implant of the present application has good physical properties and compressive strength.
[0103] The compressive strength of comparative example 1 is 62.4 MPa, and the compressive strength of comparative example 2 is 63.7 MPa. It can be seen that single sodium alginate or HPMC cannot achieve the compressive strength improvement that the combination of the two can bring to the 3D printed implant, while the combination of the two has a synergistic effect to improve the compressive strength of the 3D printed implant.
[0104] The compressive strength of Comparative Example 3 is 68.1 MPa, and the compressive strength of Comparative Example 4 is 64.6 MPa. It can be seen that the combination of polydopamine and silane coupling agent can introduce groups and coatings into the titanium alloy, thereby improving the compressive strength of the 3D printed implant using titanium alloy as one of the raw materials.
[0105] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a surface functionalized 3D printed implant, characterized in that: The steps include: S1: Preparation of PVA / PEG / GO hydrogel Weigh PVA solid, add deionized water, seal, heat, and stir to obtain a PVA solution; weigh PEG powder, dissolve it in deionized water, and stir to obtain a PEG solution; mix the PVA solution, PEG solution, and GO solution to obtain a PVA / PEG / GO hydrogel; S2: Preparation of Ti6Al4V composite powder Sodium alginate, HPMC and deionized water are mixed, heated and stirred to obtain a premixed liquid, Ti6Al4V powder is weighed, heated, and then all added to the premixed liquid, and a foaming agent is added and stirred to obtain a Ti6Al4V composite slurry, the Ti6Al4V composite slurry is poured into a mold, and low-temperature solidified to obtain a Ti6Al4V composite embryo body, the Ti6Al4V composite embryo body is sintered, and then crushed, sieved, and granulated to obtain a Ti6Al4V composite powder; S3: Preparation of 3D printed implants S3.1: stirring the PVA / PEG / GO hydrogel and adding the Ti6Al4V composite powder to obtain a composite titanium alloy slurry, adding the composite titanium alloy slurry into a syringe for 3D printing, drying, then degreasing, and sintering to obtain a 3D printed implant; S4: Surface treatment of 3D printed implants S4.1: Sodium hydroxide, sodium dihydrogen phosphate, disodium ethylenediaminetetraacetic acid, calcium acetate and deionized water are mixed to prepare an electrolyte, a 3D printed implant is placed in the electrolyte, the 3D printed implant is used as an anode and the electrolytic cell is used as a cathode, and an electric current is applied to obtain an electrically treated 3D printed implant, the electrically treated 3D printed implant is immersed in a sodium hydroxide solution, heated, then taken out, immersed in a mixture of a polydopamine solution and a silane coupling agent, then taken out, rinsed with deionized water, and dried to obtain a 3D printed implant with surface functionalization treatment.
2. The method for preparing a surface functionalized 3D printed implant according to claim 1, characterized in that: Step S1 of preparing PVA / PEG / GO hydrogel comprises the following steps: S1.1: Weigh 10-12 parts by mass of PVA solid, add 80-90 parts by mass of deionized water, seal, heat to 70-80°C, and stir at a speed of 50-60 r / min until all the PVA is dissolved to obtain a PVA solution; S1.2: Weigh 20-25 parts by weight of PEG powder, dissolve it in 80-85 parts by weight of deionized water, and stir for 1-5 minutes to obtain a PEG solution; S1.3: PVA solution, PEG solution and GO solution were mixed in a volume ratio of (4-6):(2-5):1, heated to 60-70°C, and ultrasonically treated for 10-20 min to obtain PVA / PEG / GO hydrogel.
3. The method for preparing a surface functionalized 3D printed implant according to claim 1, characterized in that: Step S2 of preparing Ti6Al4V composite powder comprises the following steps: S2.1: 1-5 parts by mass of sodium alginate, 0.5-3 parts by mass of HPMC and 95-100 parts by mass of deionized water are mixed, heated to 80-90° C., and magnetically stirred at a speed of 400-450 r / min for 2-2.5 h to obtain a premixed solution; S2.2: Weigh 5-10 parts by mass of Ti6Al4V powder, heat it to 80-90°C, then add all of it to the premixed liquid, heat it in a water bath to maintain the temperature at 80-90°C, continue stirring for 30-35 minutes, then add 8-12 parts by mass of a foaming agent, stir for 10-20 minutes, and obtain a Ti6Al4V composite slurry; S2.3: pouring the Ti6Al4V composite slurry into a mold and curing it in a low temperature environment of 0-4°C for 10-12 hours, and then maintaining the temperature at 15-20°C for air drying for 24-26 hours to obtain a Ti6Al4V composite embryo; S2.4: The Ti6Al4V composite body is placed in a vacuum sintering furnace in an argon atmosphere for sintering at a temperature of 1000-1400°C. After sintering, it is naturally cooled to room temperature 24°C, and then crushed through a 100-mesh sieve and granulated to obtain a Ti6Al4V composite powder.
4. The method for preparing a surface functionalized 3D printed implant according to claim 3, characterized in that: The foaming agent is fatty alcohol polyoxyethylene ether.
5. The method for preparing a surface functionalized 3D printed implant according to claim 1, characterized in that: Step S3 of preparing a 3D printed implant comprises the following steps: S3.1: PVA / PEG / GO hydrogel was stirred at a speed of 1500-1600 r / min, and Ti6Al4V composite powder was added. The mass ratio of PVA / PEG / GO hydrogel to Ti6Al4V composite powder was 9: (10-12), stirring for 20-25 min to obtain a composite titanium alloy slurry; S3.2: Add the composite titanium alloy slurry into the syringe, select a printing head with a diameter of 0.5 mm, set the extrusion speed to 1000 mm min-1, and print out the titanium alloy stent blank according to the planned path. The stent size is set to 30 mm in length, 30 mm in width, and 10 mm in height. The diameter of a single wire is 0.5 mm, and the stent hole type is a vertical orthogonal structure. Place the stent blank in a drying oven at 65-70 °C for 6-8 h, and then place it in a vacuum oven less than 2 × 10 -2 Debinding and sintering are completed in a vacuum tube furnace of 1.5 Pa and kept warm for 2-2.5 h to obtain a 3D printed implant.
6. The method for preparing a surface functionalized 3D printed implant according to claim 5, characterized in that: The sintering temperature in the vacuum tube furnace is 1100-1350℃.
7. The method for preparing a surface functionalized 3D printed implant according to claim 1, It is characterized in that The 3D printed implant surface treatment in step S4 includes the following steps: S4.1: 0.2 mol / L sodium hydroxide, 0.04 mol / L sodium dihydrogen phosphate, 0.015 mol / L disodium ethylenediaminetetraacetate, 0.1 mol / L calcium acetate and deionized water are mixed in a volume ratio of 2:3:1:1:(8-10) to prepare an electrolyte, the 3D printed implant is placed in the electrolyte, the 3D printed implant is used as the anode and the electrolytic cell is used as the cathode, the temperature is maintained at 30-35°C, and a pulsating power supply is applied for 5-10 minutes to obtain an electrically treated 3D printed implant; S4.2: Immerse the electrically treated 3D printed implant in a 5 mol / L sodium hydroxide solution, in a water bath at 65-70°C for 24-26 hours, then heat to 80-90°C, take it out, immerse it in a mixture of polydopamine solution and silane coupling agent for 1-1.5 hours, then take it out, rinse it with deionized water 3 times, and dry it at 60-80°C for 4-5 hours to obtain a 3D printed implant with surface functionalization treatment.
8. The method for preparing a surface functionalized 3D printed implant according to claim 7, characterized in that: The silane coupling agent is 3-aminopropyltriethoxysilane.
9. The method for preparing a surface functionalized 3D printed implant according to claim 7, characterized in that: The volume ratio of the polydopamine solution to the silane coupling agent is 3:
1.
10. A surface functionalized 3D printed implant, prepared by the method for preparing a surface functionalized 3D printed implant according to any one of claims 1 to 9.